금융위기의 고용파급효과에 대한 실증분석 - 신석하 (12711, 2012)
This paper analyzes how the adverse impacts of the global financial crisis on Korea’s employment could be mitigated in comparison with the Asian crisis period. The results from error-correction models suggest that the less severe impacts during the globa